Digital Marketing on Purchasing Decisions: Exploring the Sustainable Marketing Dynamics - Sharma, Sabita (Academia Journal of Humanities & Social Sciences, 2026)
The main objective of this paper is to examine the impact of digital marketing on the consumer purchase decisions, with a particular focus on the online purchasing behavior, product reviews, social media influence, and customer loyalty. A descriptive cross-sectional analytical study with a sample size of 100 with semi-structured questionnaires has been employed to assess the role of digital marketing on the purchase decisions. Out of the total respondents, majority are the young group of people with 59 percent, mostly having the secondary level of education and engaged in services, with 60 percent of respondents frequently purchase through online on the weekly basis and nearly half of respondents had the influence of digital marketing like social media, including the product reviews on their purchasing habit. The study also shows the relationship between the purchasing frequency and loyalty toward their businesses that provide the regular order updates and advertisements of their product. The study concludes that the effective digital marketing practices, particularly the transparent communication and customer engagement, play a vital role in shaping the purchase decisions and in fostering a long term consumer loyalty.